Biotechnology of penaeid shrimps : perspectives on physiology of growth, reproduction and disease therapeutics - Diwan, A. D. (Boca Raton : CRC Press, 2021)
The main objective of this bookis to collect comprehensive information on various aspects of physiology and biotechnology focusing mainly on reproduction, growth, disease control and therapeutics of penaeid shrimps. The book covers fundamental aspects and few applied aspects of biotechnology concerning basic genomics and proteomics, reproduction, growth and disease control and therapeutics of shrimp. This information will be quite useful not only to the aqua-farmers/mariculture experts of the shrimp industry to augment quality shrimp production in captive condition but also to the faculties and students working in different organizations involved in teaching and research activities in shrimp biotechnology.Note: T&F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
1. Basics of Genomics in Shrimp 2. Basics of Proteomics in Shrimp 3. Physiology of Reproduction 4. Neuroendocrine System in Shrimps 5. Neuroendocrine Control of Maturation, Breeding and Spawning 6. Gamete Physiology and Cryopreservation of Gametes, Embryos and Larvae 7. Artificial Insemination Technique for Inducement of Larval Production 8. Physiology of Growth and Moulting 9. Neuroendocrine Control of Moulting and Growth 10. Immune System and Mechanism of Defence 11. Diseases in Shrimp and Current Diagnostic Methods 12. Disease Control in Shrimps and Therapeutics.
OCLC-licensed vendor bibliographic record.
Keywords: Penaeidae -- Physiology; Penaeidae -- Growth; Penaeidae -- Diseases; Marine biotechnology; SCIENCE / Life Sciences / General; SCIENCE / Life Sciences / Biology / Marine Biology